Marketing Dataveillance and Digital Privacy: Using Theories of Justice to Understand Consumers’ Online Privacy Concerns - Ashworth, Laurence (Journal of business ethics, 2006)
Technology used in online marketing has advanced to a state where collection, enhancement and aggregation of information are instantaneous. This proliferation of customer information focused technology brings with it a host of issues surrounding customer privacy. This article makes two key contributions to the debate concerning digital privacy. First, we use theories of justice to help understand the way consumers conceive of, and react to, privacy concerns. Specifically, it is argued that an important component of consumers’ privacy concerns relates to fairness judgments, which in turn comprise of the two primary components of distributive and procedural justice. Second, we make a number of prescriptions, aimed at both firms and regulators, based on the notion that consumers respond to perceived privacy violations in much the same way they would respond to an unfair exchange.